Literasi Keuangan dan Uang Saku Sebagai Keputusan Berinvestasi: Perilaku Keuangan - Surahman, Dedy; Oktaviani, Marista; Setiawan, Adhar Putra; Sa’diyah, Halimatus (Akuntansi & Ekonomika, 2023)
This research shows that financial literacy and pocket money influence investment decisions and financial behavior. The research object was FEB students at the Muhammadiyah University of Surabaya; the research sample was 350 FEB students. Data collection uses primary data in the form of a questionnaire, which is filled with research instruments according to the indicators of the variable. Data processing using SEM-PLS tests hypotheses with outer and inner models. The results of the study show that financial literacy, pocket money, and financial behavior have no significant effect on investment decisions, while financial literacy and pocket money have a significant effect on financial behavior.